Health risk assessment of polycyclic aromatic hydrocarbons in common food crops within and outside selected mining areas of Ebonyi State, Nigeria - Okechukwu N.N. Okoye; Ikechukwu K. Ijoma; David Okechukwu Okeke (Scientific Reports)
Abstract The study reveals the level of polycyclic aromatic hydrocarbons (PAHs) in three local food crops planted within six selected mining sites in the State, compared with those that were planted 500 m away from the mining areas. Gas Chromatography-Flame Ionization detection (GC-FID) model was used to determine the PAHs content in the food crop samples. Mann-Whitney U Test Analysis, was used as the statistical tool to check for the significant difference between the PAH level in food crops within and 500 m away from the mining site, in order to determine the impact of the mining practice carried out in those sites on the cultivated food crops in those areas to PAHs contamination. The result of the analysis clearly showed a significant difference between the PAH level in the food crops grown within the mining area, and the ones grown 500 m away from the mining sites. BaP (Benzopyrene) equivalent concentration (BEC) and daily intake dosage (DDI). Also excess cancer risk (ILCR) were used to calculate the carcinogenic exposure limits and cancer risk evaluations from these food crops for the children and adults: with overall values of 2.01E-08, 6.01E-09, 1.54E-08, 8.08E-09, 7.90E-08, 1.26E-08, 1.94E-08, 6.26E-09, 8.63E-09, 5.74E-09, 1.23E-08, 3.90E-09 and 4.30E-09, 1.29E-09, 3.31E-09, 1.73E-09, 1.69E-08, 2.70E-09, 4.16E-09, 1.34E-09, 1.85E-09, 1.23E-09, 2.63E-09, 8.35E-10 respectively; for Enyigba, Ezza South, Ikwo, Akwatakwa, Ameri Ameka, Mpume-Akwaokuko. The increase of some of these PAHs such as Benzo (a) pyrene (BaP), 1,2-benzanthracene (BENA), benzo(k)fluoranthene (BkFLO), dibenzy (a, h)anthracene (DahANT) and benzo(b)fluoranthene (BbFLO), being carcinogenic and genotoxic, posed a great health risk to the indigenes/consumers of these food crops. Therefore, it becomes very important to enforce proper mining policies and practices in order to reduce the contamination of these PAHs on food crops. ILCR values gotten from across the six mining sites (sites A) were higher than those 500 m away sites B), even though these values when compared with the USEPA acceptable guideline value of 0.000001 (10−6), fell within the USEPA acceptable limit. However, the accumulation of these PAHs in the body tissues and organs, especially in young children, over the years, will expose consumers of these contaminated food crops in these mining areas, to PAH-related diseases, which can be very fatal.